Karakteristik Semen Ayam Kampung Yang Diberi Minyak Hati Ikan Kod Sebagai Feed Suplement - Khaeruddin Khaeruddin; Arismunandar Arismunandar; Nurda Nurda (Musamus Journal of Livestock Science, 2020)
This study aims to determine the effect of cod liver oil (MHK) supplementation in the ration on the quality of native chicken spermatozoa. Eight native chickens are kept in individual cages which are given MHK treatment as much as 0.7% of the total ration. Two weeks of maintenance. Semen was collected before treatment and four weeks after treatment. The parameters observed were macroscopic and microscopic characteristics of fresh semen before and after treatment. The results showed there were no differences in semen volume, semen color, semen pH, semen consistency, spermatozoa motility, spermatozoa viability and spermatozoa abnormalities before and after treatment. However, mass movement and spermatozoa concentration decreased after MHK supplementation treatment. The conclusion of this study is MHK supplementation did not affect the general characteristics of semen with the exception of mass movement and concentration of native chicken spermatozoa.